Echocardiographic Imaging of Intracardiac Thrombus and Evaluated its Underlying cause along Therapeutic Implications: A Review (University Heart Journal, 2020)
Abstract not availableUniversity Heart Journal Vol. 16, No. 1, Jan 2020; 40-42